2012
DOI: 10.1038/npp.2012.146
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Integrity in Highly Traumatized Adults With and Without Post-Traumatic Stress Disorder

Abstract: Prior structural imaging studies of post-traumatic stress disorder (PTSD) have observed smaller volumes of the hippocampus and cingulate cortex, yet little is known about the integrity of white matter connections between these structures in PTSD samples. The few published studies using diffusion tensor imaging (DTI) to measure white matter integrity in PTSD have described individuals with focal trauma rather than chronically stressed individuals, which limits generalization of findings to this population; in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 53 publications
9
115
2
Order By: Relevance
“…In contrast, previous studies have reported decreased cingulum FA of PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011). These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, previous studies have reported decreased cingulum FA of PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011). These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls.…”
Section: Discussionmentioning
confidence: 70%
“…FA is a measure sensitive to alterations in axonal directionality and white matter organization (Beaulieu, 2009). Reduced FA in the cingulum bundle has frequently been reported in PTSD patients (Fani et al, 2012;Kim et al, 2005;Sanjuan et al, 2013;Schuff et al, 2011), although heightened FA in the cingulum bundle has also been reported (Abe et al, 2006;Zhang et al, 2012). One longitudinal study has investigated white matter microstructure in a small sample of only eight PTSD patients, 10 and 24 months after experiencing a traumatic event ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this inflammation-induced amygdala response may also contribute to the association between increased CRP levels and heightened psychophysiological hyperarousal in traumatized individuals with PTSD (Michopoulos et al, 2015b). The hippocampus is another brain structure within the medial temporal lobe whose function, structure, and functional connectivity with other regions is comprised in individuals with PTSD, GAD, and PD (Cui et al, 2016;Fani et al, 2012b;Woon et al, 2010). Hippocampal alterations, including smaller hippocampal volume, are associated with both emotional and cognitive deficits in individuals with PTSD (Bremner, 2006).…”
Section: Consequences Of Increased Inflammation In Fearand Anxiety-bamentioning
confidence: 99%
“…10,11 In line with the prevailing neurocircuitry model of PTSD, lower white matter integrity of tracts connecting the prefrontal cortex with limbic regions, including the cingulum bundle and uncinate fasciculus, has been associated with PTSD and its development. [12][13][14] The uncinate fasciculus connects the orbital, medial and lateral prefrontal cortex with rostral temporal areas, including the anterior temporal lobe, parahippocampal…”
Section: Introductionmentioning
confidence: 99%